2018
DOI: 10.1074/jbc.ra118.003936
|View full text |Cite
|
Sign up to set email alerts
|

Receptor recognition by the peroxisomal AAA complex depends on the presence of the ubiquitin moiety and is mediated by Pex1p

Abstract: The receptor cycle of type I peroxisomal matrix protein import is completed by ubiquitination of the membrane-bound peroxisome biogenesis factor 5 (Pex5p) and its subsequent export back to the cytosol. The receptor export is the only ATP-dependent step of the whole process and is facilitated by two members of the AAA family of proteins (ATPases associated with various cellular activities), namely Pex1p and Pex6p. To gain further insight into substrate recognition by the AAA complex, we generated an N-terminall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 82 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…The three modules of Ant1p contain hydrophilic loops showing an excess of positively charged residues, suggesting that the essential requirements for mitochondrial targeting should be fulfilled. In fact, we found that in wild type yeast cells, an EFGP-Ant1p fusion protein co-localized with peroxisomes visualized with reporter protein mCherry-SKL [ 61 ]. However, the same protein showed a clear mitochondrial localization in the cells of a pex19Δ deletion strain (Additional file 5 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The three modules of Ant1p contain hydrophilic loops showing an excess of positively charged residues, suggesting that the essential requirements for mitochondrial targeting should be fulfilled. In fact, we found that in wild type yeast cells, an EFGP-Ant1p fusion protein co-localized with peroxisomes visualized with reporter protein mCherry-SKL [ 61 ]. However, the same protein showed a clear mitochondrial localization in the cells of a pex19Δ deletion strain (Additional file 5 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The recycling process requires activities of other membrane bound peroxins, ubiquitinlabeling of the receptor as well as ATP-hydrolysis. The releasing process is initiated by cysteine-dependent monoubiquitination at the N-termini of Pex5p or Pex18p (Platta et al, 2007;El Magraoui et al, 2013;Schwerter et al, 2018). In the cytosol, several ways exist to remove the thioether-linked ubiquitin from the receptor (Grou et al, 2009;Debelyy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this would support the idea that the PEX1 binding engages the ubiquitin part of H 6 -PEX5-Ub-Strep. This has also been shown recently using a photo-crosslinking approach in an in vitro export assay 31 or in an assay with purified yeast proteins 53 . Thus, it seems likely that H 6 -PEX5-Ub-Strep provides binding-sites for the docking and REM proteins.…”
Section: Discussionmentioning
confidence: 54%
“…While this manuscript was under review similar findings, i.e . the result that the AAA ATPases Pex1p and Pex6p interact with N-terminally linked ubiquitin-Pex5p fusion protein were reported for the yeast proteins 53 .…”
Section: Discussionmentioning
confidence: 84%